The Effectiveness of Social Media in Enhancing Performance of Regional Apparatus in East Java - Assagaf, Aminullah; Muttaqin, Zainal; Sukesi, Sukesi (Universitas Muhammadiyah Palu, 2024)
This study aims to analyse the effectiveness of social media as a mediator in improving the performance of regional apparatus in East Java. In the digital era, social media has become an important tool in optimising government communication, transparency and accountability. This study uses a quantitative methodology with a survey approach to collect data from regional apparatus in East Java. Data were collected through questionnaires distributed to regional apparatus employees and analysed using path analysis techniques. The results The research findings indicate that the achievements of local apparatus in East Java, as well as the utilization of social media, are significantly influenced by CETTAR work culture, technological literacy, and service innovation. CETTAR work culture, technological literacy, and service innovation all showed a positive influence on social media usage and local apparatus performance. The implications of this study suggest that optimising the use of social media is an integral part of employee performance improvement strategies undertaken by local governments.